Simulation of FTTH (Fiber To The Home) Access Network Model with Optisystem on the Ngabang STO Link - Pangalayo, Jhoni David; Imansyah, Fitri; Suryadi, Dedy (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2025)
In the rapidly evolving digital era, the demand for super-fast internet continues to increase. FTTH (Fiber To The Home) is a solution with fiber optics that provides a direct connection to the customer's home, offering high bandwidth and stable internet speeds. This study simulates an FTTH access network using Optisystem software to evaluate network feasibility through parameters such as power link budget, rise time budget, BER, and Q-Factor. The simulation results show excellent network performance, with minimal difference between the calculation and simulation results, especially at the downstream side receiver attenuation value (Prx). All grades still meet the set eligibility standards. Testing of the rise time budget with NRZ coding shows results below the specified limits. The analysis of the eye diagram on the BER Analyzer shows excellent acceptability quality with a wide eye-height opening. The performance of the FTTH network is rated as excellent based on the results of calculations, simulations, and direct measurements in the field, although there are slight differences caused by factors such as safety margin values and attenuation of network components. In conclusion, simulations using OptiSystem are effective in measuring and ensuring the feasibility of FTTH access networks.